Altered Basal Ganglia Network Integration in Schizophrenia - Duan, Mingjun; Chen, Xi; He, Hui; Jiang, Yuchao; Jiang, Sisi; Xie, Qiankun; Lai, Yongxiu; Luo, Cheng; Yao, Dezhong (Frontiers in Human Neuroscience, 2015)
The basal ganglia involve in a range of functions which are disturbed in schizophrenia. This study decomposed the resting-state data of 28 schizophrenia patients and 31 healthy controls with spatial independent component analysis and identified increased functional connectivity in the bilateral caudate nucleus in schizophrenia. Further, the caudate nucleus in schizophrenia showed altered functional connection with the prefrontal area and cerebellum. These results identified the importance of basal ganglia in schizophrenia. Clinical Trial Registration: Chinese Clinical Trial Registry. Registration number. ChiCTR-RCS-14004878.